Seronegative granulomatosis with polyangiitis presenting as an acute skull base osteomyelitis with multiple cranial neuropathies. Issue 10 (20th October 2021) - Lotfallah, Andrew; Shahidi, Shayan; Odelberg, Sven Wilhelm; Darr, Adnan; Mathews, John
Abstract: Granulomatosis with polyangiitis (GPA, formerly Wegener's) is a rare form of vasculitis, commonly affecting the upper and lower respiratory tract with simultaneous glomerulonephritis. Ear, nose and throat (ENT) manifestations account for the majority of presentations. The presence of antineutrophil cytoplasmic antibody is a recognized hallmark of GPA, but clinicians should remain cautious of false negative results. We describe a rare case of GPA presenting with concurrent middle ear disease and multiple lower cranial nerve palsies. Clinical judgment was affected by repeated negative autoimmune screens, and a definitive diagnosis was only achieved following renal biopsy. Reported cases of GPA presenting with mastoiditis or cranial nerve involvement are typically seropositive, with seronegative GPA following a less aggressive process. This case highlights the importance of clinical suspicion in the face of treatment resistant ENT pathology, and the need for early histopathological analysis. Early diagnosis and treatment are crucial in limiting disease progression.